Effect of Ohmic Heating on the Rheological Characteristics and Electrical Conductivity of Mulberry (Morus nigra) Puree - Gemala Hardinasinta; Salengke Salengke; Mursalim Mursalim; Junaedi Muhidong (Polish Journal of Food and Nutrition Sciences)
The effect of temperatures (30–90°C) and concentrations (50% and 100%) on rheological parameters of mulberry puree processed with ohmic heating (OH) were evaluated. The electrical conductivities of mulberry puree ranged from 0.022 to 0.102 S/m for 50% puree and 0.052 to 0.185 S/m for 100% puree. The best model for rheological parameters of mulberry puree was the power law model (R²>0.90). The effects of OH treatment and temperature of puree on the flow behavior index (n) were insignificant (p≥0.05). However, a significant difference (p<0.05) between consistency coefficient (K) of OH-treated and control sample was observed in 100% puree. The pseudo activation energy (E a ) of ohmic-treated puree was 9.67 kJ/mol for 50% puree and 3.69 kJ/mol for 100% puree, both of these values were significantly lower than that of the unprocessed 100% puree (16.07 kJ/mol). The obtained Ea indicates that after undergoing ohmic heating pretreatment, consistency coefficient of mulberry puree became less sensitive to temperature.